On Democratic Politics A Selection of Essays by Norbert Lechner - Bobes, Velia Cecilia; Valdés-Ugalde, Francisco (Latin America Research Commons, 2023)
The German-born, Chilean author Norbert Lechner remains one of Latin America's most prominent and creative social scientists. His work is indebted to the intense debates regarding theories of modernization, developmentalism, and dependence that took place in Latin American intellectual and political circles. These theoretical sources were present as a cognitive horizon in his essential writings, and many of the central concerns that enlivened his oeuvre arose from his intellectual immersion in these deliberations. If the confrontations with the revolutionary discourses of the 1960s informed his vision of the Latin American state, his experience with authoritarianism led him to pose a question that would become central to all his career: What does it mean to do politics, and what does it mean to do democratic politics? This anthology, which includes the first translations into English of three of his most outstanding works can guide our readers, like Ariadne's thread, through the intellectual output of this great thinker. It should also be said that these writings contain some of the most intellectually stimulating approaches to political sociology written in Latin America. Published between the 1980s and the first decade of the 2000s, the texts cover a span of more than thirty years during which the author developed a very personal vision as he sought to understand politics in a different way.